Analysing Groundwater Governance in Uzbekistan through the Lenses of Social-Ecological Systems and Informational Governance - Sylvia Schmidt; Ahmad Hamidov; Ulan Kasymov (International Journal of the Commons, 2024)
Worldwide, groundwater is often poorly understood and misgoverned due to difficulties in monitoring and collective action organisation. Problems occur due to groundwater’s invisible nature, consequent poor groundwater understanding, and systemic institutional failures. In Central Asia, groundwater coordination is important at local as well as national levels, considering regional water competition since state transitions. Historic water overuse further emphasises a need for groundwater coordination between states. Information on aquifer status is often publicly unavailable and rarely shared, even between national governmental agencies. Considering the region’s arid climate and dependence on glacial melt for seasonal flows, protection of groundwater is vital to ensure water access amid pressures such as climate change. Groundwater has historically provided drinking water, with recent increased use as an alternative water source for the agriculture sector. Institutional failures in groundwater governance can be understood as “soft limits” to adaptation in the region, which governance capacity improvements could ameliorate. To understand the current status of Central Asian groundwater governance through an illustrative case of Uzbekistan, we consider its social-ecological system, associated problems (e.g., pollution, and overexploitation), and institutional context. This paper summarises findings specific to Uzbekistan from a systematic literature review on the subject in Central Asia, outlining governance challenges and opportunities. Informational governance is analysed and reveals a clear impact on groundwater use and outcomes. They include: i) uncertainty over status (i.e., quantity and quality); ii) governance complexities at various levels due to multiple knowledges; iii) power constellations and a lack of cooperation suggest increased uncertainty; iv) interest in information reform. Public data access and coordination across the region should better support collective action at local levels, reduce governance complexities, and reduce status quo hierarchies.